Transtibial Versus Anteromedial Portal Technique for Femoral Tunnel Drilling in Primary Single-Bundle Anterior Cruciate Ligament Reconstruction: A Meta-analysis of Level 1 and 2 Evidence of Clinical, Revision, and Radiological Outcomes. Issue 1 (January 2023) - Mao, Yunhe; Zhang, Kaibo; Li, Jian; Fu, Weili
Background: Although numerous clinical studies have compared transtibial (TT) and anteromedial portal (AMP) drilling of femoral tunnels during anterior cruciate ligament reconstruction (ACLR), there is no high-quality, evidence-based consensus regarding which technique affords the best outcome. Hypothesis: There would be no difference between the TT and AMP techniques in terms of knee stability, patient-reported outcomes, incidence of revision, and radiological results. Study Design: Meta-analysis; Level of evidence, 2. Methods: The PubMed and EMBASE databases were searched from inception to February 1, 2021. Level 1 and 2 clinical trials that compared TT and AM techniques were included. Data were meta-analyzed for the outcome measures of knee stability, patient-reported functional outcomes, incidence of revision, and radiological results. Dichotomous variables were presented as odds ratios (ORs), and continuous variables were presented as mean differences (MDs) and standard mean differences (SMDs). Results: The meta-analysis included 18 clinical studies, level of evidence 1 or 2, that involved 53, 888 patients. Pooled data showed that the AMP group had a lower side-to-side difference (SMD, 0.22; 95% CI, 0.06 to 0.39; P = .009), a lower incidence of pivot-shift phenomenon (OR, 3.69; 95% CI, 1.26 to 10.79; P = .02), and a higher postoperative Lysholm score (SMD, −0.26; 95% CI, −0.44 to −0.08; P = .005) than the TT group. However, no statistically significant differences were seen in other outcomes, including subjective International Knee Documentation Committee scores (SMD, –0.11; 95% CI, –0.30 to 0.09; P = .30) or grades (OR, 0.93; 95% CI, 0.35 to 2.49; P = .89), postoperative activity level (MD, –0.14; 95% CI, –0.42 to 0.15; P = .35), and incidence of revision ACLR (OR, 1.04; 95% CI, 0.93 to 1.16; P = .45). The TT technique was more likely to create longer (SMD, 1.05; 95% CI, 0.05 to 2.06; P = .04) and more oblique (SMD, 0.81; 95% CI, 0.51 to 1.11; P < .001) femoral tunnels than the AMP technique, and a higher height ratio of the aperture position was detected with the TT technique (SMD, −3.51; 95% CI, −5.54 to −1.49; P < .001). Conclusion: The AMP technique for ACLR may be more likely to produce better knee stability and improved clinical outcomes than the TT technique, but no difference was found in the incidence of revision between the 2 groups.